2019
DOI: 10.20882/adicciones.1265
|View full text |Cite
|
Sign up to set email alerts
|

Asociación entre los estados de ánimo negativo, el consumo de sustancias psicoactivas y el bullying en adolescentes escolarizados

Abstract: Objective: mental health problems during adolescence lead to increased morbidity and mortality. We intend to test the hypothesis that bullying and addictive substance use is related to negative mood states. Methods: We carried out a cross-sectional study among high school students in Burela (Northern Spain) (n=238). "Negative mood state" was defined as experiencing the following: feeling tired, sad, out of place, bored, hopeless, nervous or lacking sleep. Independent variables were binge drinking, having smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
0
9
1
2
Order By: Relevance
“…In our study, Catalonian students had lower prevalence of bullying but higher prevalence of negative mood than Galician students. This contradicts findings from previous studies carried out with Galician students, which concluded that negative mood is associated with bullying [31]. This difference could stem from the multicultural characteristics of this population, where we hypothesize that students from Burela who participated in our study differ culturally from the participants of earlier studies.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In our study, Catalonian students had lower prevalence of bullying but higher prevalence of negative mood than Galician students. This contradicts findings from previous studies carried out with Galician students, which concluded that negative mood is associated with bullying [31]. This difference could stem from the multicultural characteristics of this population, where we hypothesize that students from Burela who participated in our study differ culturally from the participants of earlier studies.…”
Section: Discussioncontrasting
confidence: 99%
“…This could explain why no differences appeared in cannabis consumption in the multivariate analyses. On the other side, a higher socioeconomic level is known to contribute to increased substance consumption [31]. In our study, although the Catalonian and Galician (Burela) municipalities have similar personal income tax (PIT), Catalonian adolescents had a higher FAS, probably due to scale characteristics and cultural reasons and, thus, this could have induced the differences in cannabis consumption.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations